Effect of subconjunctival glucose on retinal ganglion cell survival in experimental retinal ischaemia and contrast sensitivity in human glaucoma. (12th August 2015) - Shibeeb, O'Sam; Chidlow, Glyn; Han, Guoge; Wood, John PM; Casson, Robert J
Abstract: Purpose: This study aims to evaluate the effect of subconjunctival glucose on the retinal ganglion cells (RGCs) in experimental retinal ischaemia and contrast sensitivity in humans with primary open‐angle glaucoma (POAG). Methods: First, we measured the intravitreal concentration of glucose at various time points after a subconjunctival injection of 100 μl of 50% glucose to Sprague‐Dawley rats. Next, treatment and control groups received 50% subconjunctival glucose and iso‐osmotic (8%) saline, respectively, 1 h prior to a unilateral ischaemic retinal injury; 7 days later, the damage profiles were compared using RGC and axon counts. Subsequently, we conducted a double‐blind, crossover, pilot clinical study in seven eyes of five pseudophakic subjects with severe POAG. Subjects received either 0.3 mL of 50% glucose subconjunctivally or iso‐osmotic (8%) saline, then vice versa after a 2–3 week 'wash‐out' period; change in contrast sensitivity from baseline was the primary outcome. Results: Subconjunctival glucose preserved approximately 60% of Brn3a‐positive RGCs in all retinal zones compared with an 80% loss in control retinas, and rescued approximately 40% of the axonal loss. In the human trial, the contrast sensitivity at 12 cycles/degree was 0.24 log units greater than baseline (95% confidence interval 0.12–0.36; P < 0.001). Conclusions: Subconjunctival glucose partially protects RGC somata and axons against an ischaemic insult and temporarily recovers contrast sensitivity in patients with severe POAG. Although an unlikely therapeutic strategy for POAG, the findings motivate further bioenergetic‐based research in glaucoma and other optic nerve and retinal diseases, where energy failure may be part of the pathogenesis.